2019
DOI: 10.1038/s41586-019-1570-z
|View full text |Cite
|
Sign up to set email alerts
|

FPR1 is the plague receptor on host immune cells

Abstract: The plague agent, Yersinia pestis, employs a type III secretion system (T3SS) to selectively destroy human immune cells, thereby enabling its replication in the bloodstream and transmission to new hosts via fleabite. The host factors responsible for the selective destruction of immune cells by plague bacteria were not known. Here we show that LcrV, the needle cap protein of the Y. pestis T3SS, binds N-formylpeptide receptor (FPR1) on human immune cells to promote the translocation of bacterial effectors. Plagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 65 publications
1
54
0
2
Order By: Relevance
“…So our findings that YopH is critical to block ROS production support the idea that YopH may also block NETosis observed after infection of human neutrophils with a TT3S-minus strain but not WT Yptb strain [88]. We also found that degranulation was not dependent on SKAP2 after integrin and GPCR activation, receptors triggered by Yersinia [18,19,[22][23][24][25]. Thus, degranulation could contribute to the partial elimination of the ΔyopH mutant observed in tissue infection of the Skap2KO mice (Fig 2A), because YopH was sufficient to reduce MMP-9 release from all three receptors tested (Fig 6A-6C).…”
Section: Plos Pathogenssupporting
confidence: 86%
See 2 more Smart Citations
“…So our findings that YopH is critical to block ROS production support the idea that YopH may also block NETosis observed after infection of human neutrophils with a TT3S-minus strain but not WT Yptb strain [88]. We also found that degranulation was not dependent on SKAP2 after integrin and GPCR activation, receptors triggered by Yersinia [18,19,[22][23][24][25]. Thus, degranulation could contribute to the partial elimination of the ΔyopH mutant observed in tissue infection of the Skap2KO mice (Fig 2A), because YopH was sufficient to reduce MMP-9 release from all three receptors tested (Fig 6A-6C).…”
Section: Plos Pathogenssupporting
confidence: 86%
“…Since ΔyopH growth was restored in gp91 phox-/mice we evaluated the ability of YopH to block ROS production downstream of three major receptor classes (integrin receptors, G-protein coupled receptor (GPCR) and FcγR) known to activate the NADPH oxidase complex, two of which may be stimulated during Yptb infection [18,19,[22][23][24][25]. BM WT neutrophils were infected with WT-Yptb, ΔyopH, Δ5, or Δ5+pYopH and stimulated with poly-RGD (a polymer of arginine-glutamate-aspartate) to trigger integrin receptors, primed with E. coli lipopolysaccharide (LPS) and then stimulated with formyl-methionyl-leucyl-phenylalanine (fMLP) to trigger GPCR, or stimulated with IgG immune complex (IC) to trigger Fcγ receptor (FcγR) ( Fig 3A-3C) [49,55,[71][72][73][74][75][76].…”
Section: Yoph Blocks Skap2-dependent and -Independent Ros Production mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Fpr1 −/mice are protected against infection by Yersinia pestis, in line with the discovery that FPR1 acts as the receptor for this pathogen, which is the causative agent of human plague. 9 Moreover, Fpr1 −/mice subjected to ischemia-reperfusion damage to the heart present reduced inflammation, cardiomyocyte apoptosis and ventricular remodeling, accompanied by the inhibition of the mitogen-activated protein kinases (MAPK) pathway. 10 Similarly, FPR1 plays a negative role in celiac disease, a highly prevalent autoimmune disorder that can be attenuated but not cured by a gluten-free diet.…”
Section: Editorialmentioning
confidence: 99%
“…At the same time, the use of FPR1 inhibitors such as mAb can enhance the immune response and alleviate infection, indicating that FPR1 plays an important role in viral pathogenesis. 67 Recently, Yang et al 68 found that Yersinia pestis invaded CHO-SIGNR1, but did not infect other CHO transducers, indicating that SIGNR1 (CD209b) is the core lipopolysaccharide receptor of Yersinia pestis . In order to verify the specificity of the interaction between Yersinia pestis and SIGNR1, the team further proved that SIGNR1 antibody, mannan, His-Mermaid, and CD66 can inhibit core LPS-SIGNR1 interaction.…”
Section: Potential Protein Targets In a Pandemicmentioning
confidence: 99%